Make way for animals! : a world of wildlife crossings - Pincus, Meeg (Millbrook Press, 2022)
"Around the world, roads have cut off animals from the resources they need to survive. Fortunately, this problem has also inspired some creative solutions! Take a tour of wildlife crossings from badger bridges to penguin pipelines"--